A Critical Analysis on the Impact of Antiplatelet Therapy in the Patency of Infrainguinal Bypass Grafts - S. Sfyroeras, George; Saleptsis, Vassileios; Argyriou, Christos; A. Antoniou, Georgios; L. Moll, Frans; D. Giannoukas, Athanasios (Current Vascular Pharmacology, 2013)
Antiplatelet therapy plays an important role in the management of atherosclerotic disease and numerous studies have shown their efficacy in the reduction of cardiovascular mortality and morbidity. Antiplatelets are given in patients subjected to lower limb bypass aiming not only to reduce cardiovascular mortality and morbidity but also improve graft patency. Various antiplatelet agents have been used for this purpose. The aim of this review article is to critically evaluate the existing evidence on the impact of antiplatelet therapy for maintaining infrainguinal graft patency and highlight the mechanisms involved along these lines.
Keywords: femoropopliteal